The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19127202
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between the Use of Epidural Analgesia during Labor and the Development of Autism Spectrum Disorder in the Offspring?—A Review of the Literature

Abstract: Autism spectrum disorders (ASDs) are multifactorial and complex neurodevelopmental conditions usually diagnosed in the early childhood. The etiology of ASDs is commonly described as a genetic predisposition combined with an environmental impact. As a result of broadening of the diagnostic criteria the prevalence of ASDs has been increasing worldwide and the search for the modifiable factors is still on-going. Epidural analgesia (ELA) provides effective pain relief during labor and is currently the most preferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In a retrospective longitudinal study, Qiu et al observed that epidural analgesia in labour (LEA) is associated with a significantly higher rate of ASD risk along with the increase in the duration of exposure to the medication used in LEA, which caused a series of controversies regarding the methodology of the study [80]. Other studies based on robust epidemiological data and sibling matching analysis claim no significant association between LEA and ASD [81][82][83]. However, in a meta-analysis by Wang et al, it has been mentioned that LEA during birth can associate offspring with more chances of developing ASD [84].…”
Section: Epidural Analgesia In Labour and Asdmentioning
confidence: 99%
“…In a retrospective longitudinal study, Qiu et al observed that epidural analgesia in labour (LEA) is associated with a significantly higher rate of ASD risk along with the increase in the duration of exposure to the medication used in LEA, which caused a series of controversies regarding the methodology of the study [80]. Other studies based on robust epidemiological data and sibling matching analysis claim no significant association between LEA and ASD [81][82][83]. However, in a meta-analysis by Wang et al, it has been mentioned that LEA during birth can associate offspring with more chances of developing ASD [84].…”
Section: Epidural Analgesia In Labour and Asdmentioning
confidence: 99%
“…21 Several publications have recently addressed a potential association between ASD in a child and its mother's use of epidural analgesia during labour, with conflicting results. 22 A large population study by Qiu et al published in 2020, including approximately 148 000 children, found a 37% increased risk for ASD after a child's exposure to maternal labour epidural analgesia, mainly when used for longer times (adjusted hazard ratio 1.37, 95% CI, 1.23 to 1.53). 23 However, this study may not have accounted for several medical risk factors for autism more common among patients who use epidural analgesia, nor does it provided a plausible mechanism to support a link.…”
Section: Introductionmentioning
confidence: 99%